Uncovering new insights into the role of the ubiquitin ligase Smurf1 on the regulation of innate immune signaling and resistance to infection - Souza-Costa, Luiz Pedro; Andrade-Chaves, Josiane Teixeira; Andrade, Juvana Moreira; Costa, Vivian Vasconcelos; Franco, Luis Henrique (Frontiers in Immunology, 2023)
Innate immunity is the body’s first line of defense against infections. Innate immune cells express pattern recognition receptors in distinct cellular compartments that are responsible to detect either pathogens-associated molecules or cellular components derived from damaged cells, to trigger intracellular signaling pathways that lead to the activation of inflammatory responses. Inflammation is essential to coordinate immune cell recruitment, pathogen elimination and to keep normal tissue homeostasis. However, uncontrolled, misplaced or aberrant inflammatory responses could lead to tissue damage and drive chronic inflammatory diseases and autoimmunity. In this context, molecular mechanisms that tightly regulate the expression of molecules required for the signaling of innate immune receptors are crucial to prevent pathological immune responses. In this review, we discuss the ubiquitination process and its importance in the regulation of innate immune signaling and inflammation. Then, we summarize the roles of Smurf1, a protein that works on ubiquitination, on the regulation of innate immune signaling and antimicrobial mechanisms, emphasizing its substrates and highlighting its potential as a therapeutic target for infectious and inflammatory conditions.